IMPROVING THE ABILITY TO UNDERSTAND THE CONCEPT OF MULTIPLICATION THROUGH THE RME APPROACH WITH THE HELP OF THE CONGKLAK GAME FOR CLASS III ELEMENTARY SCHOOL - Ummayyah, Miftakhatul; Lungdiansari, Nevananda Arica; Pratiwi, Friska Dyah Ayuk; Ermawati, Diana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
This research was carried out because it saw a lack of optimal understanding of the concept of multiplication calculations. Objective from study This namely knowing how to increase the ability to understand the concept of calculating multiplication using (Realistic Mathematic Education) RME through the innovation of the congklak game in mathematics learning. To obtain the results of this research, the research method used was Classroom Action Research (PTK). The subjects of this research were 23 grade III students at SD 2 Klaling for the 2022/2023 academic year, consisting of 7 male students and 16 female students. The data sources for this research are students and teachers. Data collection techniques include interviews, observation, tests and documentation. Data analysis techniques are quantitative and qualitative. This research was carried out through two cycles that include four stages: planning, implementation, observation, and reflection. The research results showed that in cycle I the average score was 83.63 and 88.94 with a completion percentage of 84% and 94%, while in cycle II the average score was 95.78 with a completion percentage of 100%. In this way, it can be shown that the indicators of success have been achieved in accordance with what was expected, namely that at least 70% of students obtained a score ≥ 70.